Penggunaan Smarthphone Terhadap Prestasi Belajar Siswa pada Mata Pelajaran IPA - Anita Amelia Ole; Lilis Kodina (Journal on Education, 2022)
The smartphone is a smartphone that not only functions as a communication tool but has various functions that support human life activities. Technological advances in this modern era, besides having a positive impact, there are also have negative impacts resulting from smartphone technology, which is a problem, especially among students. For example, students who are still active at school or are often found using smartphones, and not a few teachers find students carrying or playing with Smartphones during lessons in class (Amin, 2018). The research method used is quantitative, the aim is to find out whether there is a significant relationship between smartphone use and student achievement at SMP X Airmadidi. This study used a questionnaire instrument made by the researchers themselves with a total of 69 students as respondents. The results of this study indicate that there is a significant relationship between smartphone use and student achievement. This study provides recommendations or suggestions to smartphone users, especially to students who use smartphones, namely: students are expected to continue to be able to control their time when using smartphones and continue to listen to parental directions so that the achievements obtained in the odd semester of the 2021/2022 school year can be maintained in the second semester next